ROAD SAFETY EDUCATION FOR CHILDREN: RESULTS OF CHILDREN'S BEHAVIOR ON TRAFFIC PLAYGROUND AND SIMULATED TRAFFIC SITUATIONS - Dalibor Pešić; Aleksandar Trifunović; Maja Petrović (Facta Universitatis. Series, Teaching, Learning and Teacher Education, 2019)
Child pedestrians are highly represented in fatal and severe road crashes and differ in their crossing behavior from adults. Child pedestrians are disproportionately vulnerable to road trafﬁc injuries, but it is unclear which aspects of pedestrian safety behaviors develop at what age. To create effective intervention programs, research on which pedestrian safety risks occur among which age group and urban/rural areas, is needed. For these reasons, an experiment was conducted to examine the behavior of children on traffic playground and simulated traffic situations (STS). The key results this study showed children have a higher percentage of accurate responses to the STS environment, than on traffic playground. Thereby, it is important to take those ﬁndings in account when aiming to train children for road safety. The experiment represents a basis for the creation of individualized educational interventions to help children adapt to the basic traffic safety behavior rules.